Brachypodium as an emerging model for cereal–pathogen interactions. (25th March 2015) - Fitzgerald, Timothy L.; Powell, Jonathan J.; Schneebeli, Katharina; Hsia, M. Mandy; Gardiner, Donald M.; Bragg, Jennifer N.; McIntyre, C. Lynne; Manners, John M.; Ayliffe, Mick; Watt, Michelle; Vogel, John P.; Henry, Robert J.; et al.
Abstract : Background Cereal diseases cause tens of billions of dollars of losses annually and have devastating humanitarian consequences in the developing world. Increased understanding of the molecular basis of cereal host–pathogen interactions should facilitate development of novel resistance strategies. However, achieving this in most cereals can be challenging due to large and complex genomes, long generation times and large plant size, as well as quarantine and intellectual property issues that may constrain the development and use of community resources. Brachypodium distachyon (brachypodium) with its small, diploid and sequenced genome, short generation time, high transformability and rapidly expanding community resources is emerging as a tractable cereal model. Scope Recent research reviewed here has demonstrated that brachypodium is either susceptible or partially susceptible to many of the major cereal pathogens. Thus, the study of brachypodium–pathogen interactions appears to hold great potential to improve understanding of cereal disease resistance, and to guide approaches to enhance this resistance. This paper reviews brachypodium experimental pathosystems for the study of fungal, bacterial and viral cereal pathogens; the current status of the use of brachypodium for functional analysis of cereal disease resistance; and comparative genomic approaches undertaken using brachypodium to assist characterization of cereal resistance genes. Additionally, it explores future prospects for brachypodium as a model to study cereal–pathogen interactions. Conclusions The study of brachypodium–pathogen interactions appears to be a productive strategy for understanding mechanisms of disease resistance in cereal species. Knowledge obtained from this model interaction has strong potential to be exploited for crop improvement.